The effect of physical fitness, breakfast habits, and self-confidence on learning outcomes - Khasinatul Adila; Kamal Firdaus; Sepriadi Sepriadi; Liza Liza (Global Econedu, 2026)
This study aims to examine the direct, indirect, and simultaneous effects of physical fitness, breakfast habits, and self-confidence on physical education learning outcomes. A quantitative associative design with a path analysis approach was used. The population consisted of 146 students, with a purposive sample of 50 students. Data were collected through physical fitness tests, questionnaires on breakfast habits and self-confidence, and students’ report card scores. Data were analyzed using path analysis at a significance level of 0.05. The findings show that physical fitness has a significant direct effect on learning outcomes (0.435; 18.92%) and a strong indirect effect through self-confidence (total effect 78.49%). Self-confidence also has a significant direct effect (0.564), while breakfast habits show a weaker and non-significant direct effect but a small indirect contribution (3.49%). Simultaneously, all variables significantly influence learning outcomes (R² = 0.886). Physical fitness and self-confidence are key determinants of learning outcomes, with self-confidence acting as an important mediating variable.